Consolidation in the Indian banking sector: evaluation of sustainable development readiness of the public sector banks in India. (2018) - Prakash, Ajai; Kumar, Kishore; Srivastava, Ankit
Banking is a pivot in providing the right trajectory to sustainable development actions. This paper looks at issues pertaining to consolidation activity in the Indian banking industry and tests the level of sustainable development adaptation of Indian banking industry. By rating the adaptation of banks towards SD practices. The paper also considers how far these institutions have declared their actions in terms of national and international SD norms for the banking sector. For the purpose of research, information was derived from the sustainability reports, business responsibility reports, annual reports and official websites of the banking institutions. The model adopted for the study is the sustainable banking model originally proposed by Jeucken (2001). The study was conducted on all 27 public sector banks in India for the period ended March 31, 2016. The results of the study show that none of the banks lie in the sustainable typology under the higher echelons of the model. The study indicates that the public sector banking industry in India primarily lies in the defensive and preventive banking stage, signifying that the banks merely follows the adoption of the regulatory norms.